The Effect of Shopping Enthusiasm, Shopping Motivation, and Visiting Experience on Tourist Satisfaction in East Java Tourism Village - Siti Mujanah; Sumiati Sumiati; Candraningrat Candraningrat; Annisa Kaffi; Chilmaniya Baril Haq (Jurnal Bisnis dan Keuangan, 2022)
The tourism village is a government program that aims to reduce poverty in the community around the tourist village. Sustainable tourism development can be realized by developing tourist destinations from the smallest unit, namely the village level, this is because most of the tourist activities are there. This is the background of research on the influence of tourist village services on tourist satisfaction in tourist villages in East Java. This study uses quantitative methods to determine the potential for tourist satisfaction with the shopping experience in tourist villages in East Java. Researchers analyzed tourist satisfaction through questionnaires or questionnaires distributed to respondents who had experience visiting tourist villages in East Java. The conceptual framework was developed in an effort to explain and understand tourist satisfaction with the tourist village experience in East Java. Bargaining is something that is most likely to be done by tourists to buy an item they want and get a cheap and good price is a special satisfaction for tourists in shopping. But the results of the analysis that have been obtained tourists prefer to visit tourist villages to enjoy a quieter rural atmosphere.